Use of Capillary Blood in Measurement of Arterial Po2. Issue 5619 (14th September 1968) - MacIntyre, J.; Norman, J. N.; Smith, George
Abstract : In this study we investigated the possibility of obtaining accurate values of arterial Po2 from specimens of capillary blood stored in glass capillary tubes and measured in an oxygen microelectrode. It has been shown that Po2 measurements made on the Radiometer oxygen microelectrode are as accurate as those made on the macroelectrode and that the storage of blood is as satisfactory in glass capillary tubes as in glass syringes. The important feature in obtaining accurate values for arterial Po2 is the choice of the capillary bed and its method of preparation for sampling. If the ear lobe is massaged with thurfyl nicotinate (Trafuril) it is possible to obtain values of Po2 from the capillary blood which are in close agreement with arterial Po2 in normal, hyperoxic, and shocked vasoconstricted patients.